A Microlevel Wage Dataset for Eighteenth Century Denmark - Peter Sandholt Jensen; Cristina Victoria Radu; Paul Sharp (European Historical Economics Society (EHES), 2019)
Granular microdata is of growing interest within economics and economic history. We present a uniquely detailed database of 21,557 observations of wages and 30,000 observations of prices in rural Denmark for men, women and children, and for both skilled and unskilled workers over the eighteenth century. We construct nominal wages and deflate them using Allen's constant consumer baskets. The real wage series exhibits a considerable fall with the introduction of serfdom, and other changes consistent with known historical events. We present some evidence on skill premiums and gender wage gaps and offer suggestions for future work exploiting this data.
Keywords: J31; N33; N93; 330; Denmark; microdata; prices; wages